2005
DOI: 10.1021/es048181i
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Fate of Polychlorinated Biphenyls and Polycyclic Aromatic Hydrocarbons in an Agricultural Soil

Abstract: Laboratory studies are useful for understanding the behavior of persistent organic pollutants (POPs) in soil, although such investigations do not always relate directly to field conditions. Outdoor lysimeter studies may be used to overcome this problem. This work aimed to investigate the behavior of two polycyclic aromatic hydrocarbons (PAHs) (fluoranthene and benzo[a]pyrene) and two polychlorinated biphenyls (PCBs; congeners 28 and 52) in soil, using lysimeters established in 1990 atthe Agrosphere Institute (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 47 publications
6
56
0
Order By: Relevance
“…A similar trend was found in contaminated paddy soils in southern China (Bi et al, 2002). Several studies found that leaching of PCBs through the soil column should not be significant due to their relatively low water solubilities and large Kow values (Cousins et al, 1999;Doick et al, 2005). However, other studies on soil surface profiles in forest and montane areas suggest that leaching of PCBs can occur, mostly in association with DOM (Krauss et al, 2000;Moeckel et al, 2008).…”
Section: Vertical Distribution Of Pcbs and Pbdes In Agricultural Soilssupporting
confidence: 64%
“…A similar trend was found in contaminated paddy soils in southern China (Bi et al, 2002). Several studies found that leaching of PCBs through the soil column should not be significant due to their relatively low water solubilities and large Kow values (Cousins et al, 1999;Doick et al, 2005). However, other studies on soil surface profiles in forest and montane areas suggest that leaching of PCBs can occur, mostly in association with DOM (Krauss et al, 2000;Moeckel et al, 2008).…”
Section: Vertical Distribution Of Pcbs and Pbdes In Agricultural Soilssupporting
confidence: 64%
“…Doick et al (2005) reported that the half-life for BaP was 2.7 yr in soil, which might be changed by soil characteristics (the amount and quality of soil organic matter) and the environmental situation (content of oxygen and nutrients). In the SIA, the mean concentration of BaP was 0.34 mg kg −1 in surface soil, 0.11 mg kg −1 in subsurface soil, and was much higher than the natural concentrations (0.8-4.3 μg kg −1 ; Knoche et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficiency of high molecular weight PAHs biodegradation is limited because these compounds have a very low aqueous solubility and vapour pressure. 3 Cutright, 4 Cajthaml et al 5 and Doick et al 6 found that the PAHs were degraded according to first-order reaction kinetics in wastewaters and soils without biosurfactant addition. 4 -6 The studies performed by Abalos et al, 7 Yin et al, 8 Zhou and Zhu 9 and Yu et al 10 showed that biosurfactants play an important role in the degradation of PAHs from petrochemical industry wastewaters Although studies have been conducted to enhance the biodegradation of less hydrophobic PAHs using surfactants to increase their solubility by decreasing the interfacial surface tension between PAHs and the water interphase, 7,9,11,12 limited data were found for the biodegradation kinetic of hydrophobic PAHs.…”
Section: Introductionmentioning
confidence: 99%